Learning Media Needs Analysis of Science Learning and Environment through Android for Primary School Pupils - Muhammad Richsan Yamin (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
This research focuses on analysing the needs of learning media such as android as a learning media for primary school pupils and also as a means of preparing before learning. The purpose of this research was to determine the need for learning media in preparing for learning using Android for primary school pupil of 90 Pinrang. The method was used in this research was a qualitative method using a descriptive approach. The data collection technique used in this research was to use observation guidelines, documentation and structured interview techniques with research instruments in the form of questions to be asked to the informants. Data analysis in this research was to reduce the existing data into more specific data to be presented descriptively. The initial findings found that the need for learning media using Android as a means to prepare for learning at home is needed for teachers so that primary school pupils have a mental readiness and also initial knowledge to learn. In addition, the need for animative, informative, educative and interactive learning media using android as a learning tool in the classroom on science learning and environment material is also needed to support the learning process in the school.